Implementasi Pembinaan Pengelolaan Arsip di Dinas Perpustakaan dan Arsip Kabupaten Tangerang - Cynthia Calista Herlambang Putri; Siti Maryam (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2019)
Purpose of this study to find out the Analysis of Management Archives Coaching by Tangerang District Library and Archives Services. This type of research uses a descriptive qualitative research approach. Data collection techniques, namely interviews with 5 (five) informants, observation, and documentation. While data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of the study can be concluded that the activities of archiving guidance carried out by the Tangerang District Disperpusip begins with the stages of planning, coordination, preparation of materials for archiving development, and the implementation of archiving guidance activities which are divided into two types, namely technical guidance conducted classically to OPD (Regional Apparatus Organization) ) and direct assistance to the archives manager in the village. The technical guidance activity began with gathering archive managers from each OPD namely the Office and Agency after that the activity continued with the delivery of material classically with the theme "Dynamic Archive Management, That is Depreciation With the Focus of Moving Archives". In addition, the assistance was carried out by selecting archive managers from two to three villages and continued by providing direct training on how to organize files properly with the theme "Active Dynamic Archive Management". The obstacles faced in the activities of fostering archives are Human Resources and Archive management.